PROCEDIMENTO VOLTAMÉTRICO OTIMIZADO PARA DETERMINAÇÃO DE Ni2+ EM AMOSTRAS PRÉ-TRATADAS DE BIODIESEL, USANDO ELETRODO MODIFICADO COM FILME DE MERCÚRIO - Nobre, Eva Michelly Carvalho Santana (2011)
The presence of metals in biodiesel can be related to raw material, the process used to obtain biodiesel or its storage and can cause reactions of oxidation, corrosion and clogging engines, besides causing risks to human health and the environment. In this paper, we propose a procedure based on voltammetric experimental conditions suitable for the determination of Ni2+ ion in biodiesel (B100) through Square Wave Adsorptive Stripping Voltammetry, using the mercury film electrode prepared ex situ. First, the mercury film was prepared and then was conducted the analysis of a biodiesel pre-treated (digested) sample. The sample digestion was performed with microwave oven in a closed system in the presence of ultra-pure nitric acid and hydrogen peroxide. After this, ammonia buffer 0.01 mol L-1 pH 9.23 and NaOH 0.46 mol L-1 was added into the cell to adjust the pH of the sample to a final value of approximately 9.2. Finally, the chelator dimethylglyoxime (DMG) 0.01 mol L-1 was added, which acts as a complexing element to capture the Ni2+ ion. Next, several voltammetric experiments, in the absence and presence of increasing aliquots of biodiesel and standard solution of the metallic ion, were performed to optimize the analysis conditions. The results indicate that the Square Wave Adsorptive Stripping Voltammetry (VAdRSWV) appeared suitable for measurements of trace metal in Biodiesel (B100) in concentrations up to 10-8 mol L-1. The experiments carried out by successive addition of aliquots of a standard solution of Ni2+ ions provided a linear response of peak current with the concentration of metal ion. Each sample of biodiesel was analyzed in triplicate, with very satisfactory results from the analytical point of view, once we were dealing with trace element analysis, especially in terms of accuracy (recovery 105%) and precision (RSD 9.61%) for the Ni2+ metal ion, using a confidence limit of 98%.